2016
DOI: 10.1021/acs.est.5b05971
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Third Trimester Blood Trihalomethanes and Urinary Trichloroacetic Acid Concentrations among Pregnant Women

Abstract: Prenatal exposure to disinfection byproducts (DBPs) has been associated with a variety of adverse birth outcomes. However, little is known about predictors of prenatal biomarkers of exposure to DBPs among pregnant women. We aimed to identify predictors of third trimester blood trihalomethanes (THMs) and urinary trichloroacetic acid (TCAA) concentrations, two biomarkers of exposure to DBPs, among pregnant women. Blood samples, urine samples, and questionnaires on individual characteristics and water-use activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…Second, we included geographic residence setting (urban vs rural) and household income (<3000, 3000–4999, or ≥5000 Yuan/month) as additional covariates in the mixed regression models to evaluate the influence of maternal socioeconomic status. Third, to assess the influence of recent peak exposure events, we adjusted for the time interval since last showering or bathing due to their strong influence on THM concentrations. , Fourth, we included a different set of covariates in the final models based on the previous literature according to the directed acyclic graph (DAG): , maternal age (continuous), BMI at enrollment (continuous), geographic residence setting (urban vs rural), household income (<3000, 3000–4999, or ≥5000), and maternal education level (junior school and below, high school, or college and above) (Figure S2). Fifth, to assess the influence of maternal nutritional status, we included maternal weight gain during pregnancy (continuous) as a covariate in the mixed models.…”
Section: Methodsmentioning
confidence: 99%
“…Second, we included geographic residence setting (urban vs rural) and household income (<3000, 3000–4999, or ≥5000 Yuan/month) as additional covariates in the mixed regression models to evaluate the influence of maternal socioeconomic status. Third, to assess the influence of recent peak exposure events, we adjusted for the time interval since last showering or bathing due to their strong influence on THM concentrations. , Fourth, we included a different set of covariates in the final models based on the previous literature according to the directed acyclic graph (DAG): , maternal age (continuous), BMI at enrollment (continuous), geographic residence setting (urban vs rural), household income (<3000, 3000–4999, or ≥5000), and maternal education level (junior school and below, high school, or college and above) (Figure S2). Fifth, to assess the influence of maternal nutritional status, we included maternal weight gain during pregnancy (continuous) as a covariate in the mixed models.…”
Section: Methodsmentioning
confidence: 99%
“…As numerous human epidemiological studies have already demonstrated the correlation between DBP exposure and several human health impacts, including bladder cancer, birth defects, and fetal loss, CHO cells that have been frequently used in DBP toxicity study were selected in the present study to comparatively assess the in vitro toxicity of bromophenols. CHO-K1 cell line acquired from the American Type Culture Collection was used in the present study to comparatively evaluate the cytotoxicity of 4-BrPh and 2,4-DiBrPh.…”
Section: Methodsmentioning
confidence: 99%
“…Disinfection byproducts (DBPs) are a group of chemical substances unintentionally generated from the reactions of disinfectants with organic matter (mainly including natural organic matter, effluent organic matter, and emerging environmental contaminants) during the water disinfection process. They have generally been considered as one important series of food contaminants owing to their diversity and daily long-term exposure to human beings through ingestion of disinfected drinking water, beverages prepared with tap water (e.g., coffee, tea, and juices) or foods treated using disinfected water (e.g., washed vegetables and fruits). , Previous studies with different types of toxicity bioassays reported that many DBPs were potential cytotoxicants, genotoxicants, mutagens, neurotoxicants, carcinogens, and/or teratogens, despite the fact that their toxic mechanisms are not fully understood currently. Moreover, human epidemiological studies provided evidence of an association between DBP exposure and adverse birth outcomes/raised health risks of cancers (colorectal and bladder). Hence, due to the ubiquitous existence of DBPs in disinfected potable water, there is an increasing concern on the adverse effects of DBPs on human health.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 However, existing studies on the health effects of maternal exposure to PCPCs are inconclusive because of their rapid elimination (<24 h) and high within-person variability. 14−16 Considering the changes of physiological, metabolic, and behavioral factors during pregnancy, 17 understanding variations and determinants of exposure to those contemporary-use chemicals at multiple time points is a critical step in exploring their adverse health effects on mothers and fetuses.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The detections of the above chemicals in cord serum, milk samples, placental tissues, and amniotic fluid indicate the transfer of these compounds from mothers to fetuses. Recently, epidemiological reports have suggested that exposure to PCPCs during pregnancy could cause pregnancy complications , and adverse birth outcomes. , However, existing studies on the health effects of maternal exposure to PCPCs are inconclusive because of their rapid elimination (<24 h) and high within-person variability. Considering the changes of physiological, metabolic, and behavioral factors during pregnancy, understanding variations and determinants of exposure to those contemporary-use chemicals at multiple time points is a critical step in exploring their adverse health effects on mothers and fetuses.…”
Section: Introductionmentioning
confidence: 99%